49.0k views
1 vote
Someone, please help me on this one

Someone, please help me on this one-example-1
User Regal
by
4.5k points

2 Answers

2 votes

Answer:

D

Explanation:

(f + g)(x)

= f(x) + g(x)

= 4x² + 7x - 3 + 6x³ - 7x² - 5 ← collect like terms

= 6x³ - 3x² + 7x - 8

User Haldun
by
4.3k points
2 votes

Answer:

D. (f + g )( x ) = 6x³ - 3x² + 7x - 8

Explanation:

Given :-

  • f ( x ) = 4x² + 7x - 3.
  • g ( x ) = 6x³ - 7x² - 5.

To Find :-

  • ( f + g ) ( x ).

Solution :-

(f + g )( x ) = 4x² + 7x - 3 + 6x³ - 7x² - 5.

Arranging like terms.

(f + g )( x ) = 6x³ - 7x² + 4x² + 7x -5 - 3

Combine like terms.

(f + g )( x ) = 6x³ - 3x² + 7x - 8

User Jvous
by
3.8k points